Strontium (87Sr/86Sr) dating of marine shells from pliocene and pleistocene shallow marine deposits in The Netherlands: - Jansen, H.S.M.; Huizer, J.; Dijkmans, J.W.A.; Hinte, J.E. van (2004)
87Sr/86Sr (Strontium) ratio analyses of shell material (mainly Arctica islandica) from 24 levels in the Maassluis Formation of boreholes Noordwijk, Zegveld and Terschelling suggest that the age of the formation ranges from 0.82 to 2.34 Ma (± 0.5 Ma), and that the Oosterhout Formation at Noordwijk could be as much as 2.5 Ma older than hitherto assumed.